Every child matters: non-normative fatherhood of care and compassion in Malayalam cinema - Raj, Sony Jalarajan; Suresh, Adith K. (My University, 2025)
This chapter surveys the evolving portrayal of fatherhood in Malayalam cinema. The chapter examines how traditional notions of parenthood in South Indian society, often centered on biological and patriarchal roles, are being challenged by narratives of adoptive fatherhood. In analyses of films like Photographer (2006), Ottaal (2014), and Pengalila (2019), the chapter discusses how these stories depict fathers who adopt and care for marginalized children, and thereby subvert entrenched caste and class dynamics. These films serve as reflections of non-normative fatherhood in regional spaces, and underscore the significance of parental care in non-Western contexts. The chapter argues that such cinematic representations advocate for social justice, inclusivity, and empathy, challenging conventional views on family and societal norms in India. Malayalam cinema, portraying adoptive caregiving as a radical act of compassion and solidarity, offers alternative perspectives on family, inheritance, and societal belonging.
Keywords: fatherhood; Malayalam cinema; adoptive fathers; alternative perspectives; South Indian society